Profil Kondisi Fisik Dan Mental Skill Atlet Bola Tangan Kabupaten Bojonegoro - Febriti Tania Choirul Anisa (Indonesian Journal of Kinanthropology (IJOK), 2024)
Background: In handball, an athlete's ability to be successful is influenced by their physical condition and mental skills. Therefore, it is important for coaches to have information about the physical health and mental skills of their athletes. Knowing the profile of the physical condition and mental skills of handball athletes from Bojonegoro Regency is the aim of this research. Methods: This research is included in descriptive research using a post-test only design for the physical condition profile and a survey for mental skills. The instruments used are the 30 m running test for speed, the sit and reach test for flexibility, the Illinois Agility Run Test for agility, the push up test for arm muscle strength, the Medicine Ball Test for arm muscle power, the MFT for cardiac and respiratory endurance, and Mental Skills Questionnaire for evaluating mental skills when competing. Bojonegoro Regency Handball Athletes are the population in this study with a sample of 31 athletes (19 men and 12 women). Results: The research findings show that the physical condition and mental skills of Bojonegoro Regency handball athletes are in the "Medium" category with a percentage of physical condition of 50% and mental skills of 57.14% of all components of the physical condition and mental skill aspects of Bojonegoro Regency handball athletes. From these results, it is in accordance with the opinion of experts that "Sport is 90-95% mental". Conclusions: Bojonegoro Regency handball athletes show a level that is classified as “Moderate”. This shows the potential for improvement in both the physical condition and mental skills of athletes.